The Effect of coconut Fiber on the Cement Mortar Properties - Zulkarnen, Zulfadzli Yusrin; Ismail, Noorli (Recent Trends in Civil Engineering and Built Environment, 2023)
This test was conducted to replace sand as the main ingredient in the mortar mix. coconut is one of the materials widely used in the food industry in Malaysia, excess coconut fiber can be used as a recycling material to replace sand. First objective is to investigate the feasibility of using coconut fibre to replace fine aggregates. The second objective is the purpose of this test is to determine the development of compressive strength of cement mortar at various percentages of coconut fibre. Third objective is to identify the mineral composition of coconut fiber mortar. In mortar mixed work, the ratio used was 1: 2.75 and the water-cement ratio was 0.6 following the standard (ASTM C 109/C 109M-02) standards. On the other hand, several tests will be conducted on coconut fiber mortar that will be compared with control samples, which is, compressive strength, scanning electron microscopy (SEM) and X-Ray Diffraction. On the other hand, several tests will be conducted on coconut fiber mortar that will be compared with control samples, namely, compressive strength (BS EN 196-1:2005), Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). At the end of this project, it was found that the maximum was on the control sample which was 22.0 N/mm2 compared to the other samples. In addition, for mortar coconut fiber mixture has a mineral composition such as Quartz (Sio2), Aluminum iron (AlFe3), Cellulose Ibeta (C6H1005)n, Portlandite (Ca(OH)2) and Silicon oxide (SiO2). Moreover, the addition of coconut fiber in the mortar caused a very high porosity compared to the control sample due to the occurrence of hydration in the mortar. Therefore, to increase the strength of the mortar, the use of chemicals as additives to prevent porosity due to water absorption by coconut fiber is strongly encouraged to curb the occurrence of porosity and cause the mortar to decrease in strength.